Weight and weight gain of east African long-fat-tailed sheep on Rwanda research stations - Sibomana, G.; Murayi, T.; Sayers, A.R.; Wilson, R.T. (International Livestock Centre for Africa, 1989)
Data on weight and weight gain of East African long-fat-tailed sheep, starting in 1974, are analysed. Birth weights averaged 2.59 kg. Weights were 11.6 kg at 90 d, 28.0 kg at 12 mo, 29.3 kg at 18 mo and 35.4 kg at 5 yr. Preweaning daily gains varied from 94 g to 157 g in the period 1974 to 1984 and were affected by sex and birth type. Correlations between weights and repeatabilities of weights at different ages were established and are discussed in relation to breeding plans.